2004
DOI: 10.1186/1472-6785-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fitness benefits of trypsin proteinase inhibitor expression in AbstractBackground: The commonly invoked cost-benefit paradigm, central to most of functional biology, explains why one phenotype cannot be optimally fit in all environments; yet it is rarely tested. Trypsin proteinase inhibitors (TPIs) expression in Nicotiana attenuata is known to decrease plant fitness when plants compete with unattacked conspecifics that do not produce TPIs and also to decrease the performance of attacking herbivores. Results:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 63 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…Zavala and Baldwin (2004) studied the costs and benefits of TPI production in two ecotypes of N. attenuata, both of which were transformed to silence or enhance TPI production (Zavala et al 2004b). They showed that plants with low TPI production had a higher fitness than TPIexpressing genotypes when plants were not attacked, but when attacked, plants with high TPI production had an advantage over TPI-silenced plants (Zavala and Baldwin 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zavala and Baldwin (2004) studied the costs and benefits of TPI production in two ecotypes of N. attenuata, both of which were transformed to silence or enhance TPI production (Zavala et al 2004b). They showed that plants with low TPI production had a higher fitness than TPIexpressing genotypes when plants were not attacked, but when attacked, plants with high TPI production had an advantage over TPI-silenced plants (Zavala and Baldwin 2004).…”
Section: Discussionmentioning
confidence: 98%
“…This species and its specialist herbivore Manduca sexta (Sphingidae) have been developed as a model system for the study of plant-herbivore interactions (Baldwin and Preston 1999;Kessler and Baldwin 2002). In response to attack from M. sexta larvae, which is recognized when larval oral secretions (OS) are introduced into wounds during feeding (McCloud and Baldwin 1997;Halitschke et al 2001;Schittko et al 2001;Roda et al 2004), the plant dramatically increases the accumulation of trypsin proteinase inhibitors (TPI) which slow the growth of larvae (Zavala et al 2004a;Zavala and Baldwin 2004), presumably by inhibiting the function of larval digestive proteases. TPI production, however, comes at a significant fitness cost for the plant as TPI-producing genotypes are out-competed and produce less seed than genotypes in which TPI production has been genetically silenced (Glawe et al 2003;Zavala et al 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of trypsin protease inhibitors (TPIs) in Nicotiana attenuata Torr. ex Watson increases growth and fitness (Zavala et al ., 2004), but plants silenced in nicotine production function similarly to wild-type plants (Steppuhn et al ., 2004). As such, TPIs may incur greater resource costs than nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these findings suggest that plants have a potential for continued evolution of induced response. Furthermore, several studies have shown the fitness costs of maintaining inducibility in the absence of herbivores and the benefits of induction in the presence of herbivores (Baldwin 1998;Agrawal et al 2002;Tian et al 2003;Zavala and Baldwin 2004;Go´mez et al 2007; but see Karban 1993). These results suggest that herbivore-induced plant responses are likely to be adaptive under the environment with herbivores.…”
Section: Sources Of Plant Trait Variation and Structuring Arthropod Cmentioning
confidence: 58%